Relasi Qatar dengan Ikhwanul Muslimin dalam Kerangka Nested Power (State Islamic Institute of Kudus (IAIN Kudus), 2021)
The Muslim Brotherhood (MB) is an obstacle that disrupts Qatar's relations with its neighbors in the Gulf, especially Saudi Arabia and the United Arab Emirates. Qatar's different position with the fellow Gulf countries towards Muslim Brotherhood became one of the problems that caused the estrangement of the relationship. The dispute led to demands that Qatar ends its support for the Muslim Brotherhood. However, Qatar remains unmoved in maintaining good relations with the Muslim Brotherhood. This article aims to answer why Qatar retains its relationship with the Muslim Brotherhood amid the severing of diplomatic ties from fellow Gulf countries. This research uses qualitative research methods with library studies. This study uses secondary data obtained from books, journals, and the internet, which are then interpreted and concluded utilizing the concept of nested power. This article finds that Qatar maintains its relationship with the Muslim Brotherhood to maintain national political stability by accommodating the Muslim Brotherhood in government circles, especially in education and da'wah. Meanwhile, Qatar utilizes the global MB network at the regional and international levels to lift Qatar's branding as an essential actor in the Muslim world and the Globe.